تأثير اللوبي الصهيوني في السياسة الخارجية الأمركية وأثره على القضية الفلسطنية2000 -2008 -اللجنة الامركية الاسرائلية نموذجا - - سهام مراكشي (جامعة محمد بوضياف المسيلة, 2015)
2008 تناولت الدراسة تأثير اللوبي الصهيوني في السياسة الخارجية الأمريكية وأثره على القضية الفلسطينية ( 2000 خلال التعرف على مراحل تطور العلاقات الأمريكية – الفلسطينية، ودور اللوبي الصهيوني في تطور العلاقات الأمريكية- الإسرائيلية. وتداعيات العلاقة الأمريكية-الإسرائيلية على مستقبل القضية الفلسطينية خلال فترة حكم الرئيس بوش الابن، استخدمنا المنهج التاريخي حيث أن الدراسة استعرضت أحداث يحكمها عامل التغيير والتطور التاريخي، إلى جانب استخدام المنهج الوصفي التحليلي، وذلك من أجل دراسة كيفية تأثير العلاقات الأمريكية -الإسرائيلية على القضية الفلسطينية، في الأعوام 2000 م حتى 2008 م، كما استخدمنا المنهج الاستشرافي للتنبؤ بمستقبل القضية الفلسطينية في ظل هكذا علاقة بين الولايات المتحدة الأمريكية و(إسرائيل). وخلصت الدراسة إلى مجموعة من النتائج، كان أهمها: أن العلاقات السياسية الأمريكية -الإسرائيلية ترتكز على المصالح المتبادلة، فالشرق الأوسط يمثل للولايات المتحدة الأمريكية منطقة إستراتيجية هامة تؤثر على الأمن القومي الأمريكي، كذلك فإن (إسرائيل) طبقا لنظرية الأمن الإسرائيلي تعد الولايات المتحدة الأمريكية، هي الحليف الإستراتيجي الذي تعتمد عليه في صراعها مع في الولايات المتحدة، استطاع أن يؤثر في مؤسسات الرأي العام وأجهزة (AIPAC) العرب. كما أوضحت الدراسة أن اللوبي الصهيوني صنع القرار الأمريكي بما فيه مؤسسة الرئاسة ذاا، وإلى جانب التغلغل الواضح للوبي الصهيوني في مختلف المؤسسات التي تشترك في صنع القرار الأمريكي، فإن الوضع داخل دوائر الرأي العام ليس بحال أفضل خاصة تجاه العالم العربي. كما اتضح من الدراسة أن الولايات المتحدة تقوم بشكل دائم ومستمر بتقديم الدعم والمساعدات في كافة االات (لإسرائيل) وهذا يعتبر تجسيدا للعلاقات الخاصة التي تربط البلدين، ويعتبر المقصد من التعاون الأمريكي الإسرائيلي والمساعدات العسكرية الأمريكية (لإسرائيل) هو الحفاظ على التفوق العسكري الإسرائيلي في الشرق الأوسط. كما أثبتت الدراسة أن عبر المراحل التاريخية المختلفة وجود تجاهل من الإدارة الأمريكية بشكل كبير للقضية الفلسطينية، وفى المقابل تأييدها الكبير ومساندا (لإسرائيل). The study dealt with the impact of Zionist lobby in us foreign policy and their impact on the Palestinian. issue (2000 - 2008) by identifying the stages of the evolution of U.S. Palestinian relations , and the rôle of the Zionist lobby in the evolution of U.S. - Israel relations . The repercussions of the US-Israel relationship on the future of the Palestinian cause during the reign of President George W. Bush , used the historical method , where the study reviewed the events governed by a factor of change and historical development, as well as the use of descriptive analytical method , in order to study how the U.S. - Israel relations on the case Palestinian . in the years 2000 to 2008 AD as they used the forward-looking approach to predict the future of the Palestinian issue in light of such a relationship between the United States and Israel. The study found a range of results , was the most important: that political relations , U.S. - Israel based on mutual interests , the Middle East, representing the United States of America region an important stratégie impact on U.S. national security , as well as the (Israel) , according to the theory of Israeli security is the United States of America , is a stratégie ally on which it relies in its conflict with the Arabs . The study also showed that the Zionist lobby (AIPAC) in the United States , was able to affect the institutions of public opinion and decision-making bodies the U.S. , including the institution of the presidency itself, in addition to penetrate clear to the Zionist lobby (AIPAC) ’in the various institutions involved in the American decision-making , the situation within the circles of public opinion is not better off especially towards the Arab world . As it turns out from the study that the United States permanently and continuously provide support and assistance in all areas ( of Israel) and this is considered the embodiment of the special relations between the two countries , and is the destination of U.S. cooperation of the Israeli and U.S. military aid ( to Israel) is to maintain Israel's military superiority in the Middle East . The study proved that through different historical stages and ignore the existence of the U.S. administration largely to th
Keywords: العلاقات الدولية . القضية الفلسطنية .الولايات المتحدة الامركية . اللوبي الصهيوني .